2020
DOI: 10.1002/mus.27103
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in Japanese patients with ocular myasthenia gravis

Abstract: Introduction The majority of patients with myasthenia gravis (MG) initially present with ocular symptoms, but it is difficult to predict which cases will remain as ocular MG (OMG) or will progress to generalized MG. Herein we evaluated the serologic profile of Japanese OMG and its relationship with clinical features. Methods Seventy‐three patients with OMG from five Japanese myasthenia gravis (MG) centers were enrolled. Live cell‐based assays (CBAs) were used to determine the presence of autoantibodies (Abs) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…We found TNMG to present a bimodal onset distribution age, which is similar to AChR-MG 2 . Our study's mean onset age of TNMG was 32.4 y, which was younger than that of other reports (40-47.8 y), 11,13,14,23 possibly due to differences in ethnicity or inclusion criteria. Moreover, sex is an important factor affecting the bimodal age of onset, because although the overall incidence was the same for both sexes, there were differences by age group: JOMG predominantly affected female patients, while A-EOMG affected more male than female patients.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…We found TNMG to present a bimodal onset distribution age, which is similar to AChR-MG 2 . Our study's mean onset age of TNMG was 32.4 y, which was younger than that of other reports (40-47.8 y), 11,13,14,23 possibly due to differences in ethnicity or inclusion criteria. Moreover, sex is an important factor affecting the bimodal age of onset, because although the overall incidence was the same for both sexes, there were differences by age group: JOMG predominantly affected female patients, while A-EOMG affected more male than female patients.…”
Section: Discussioncontrasting
confidence: 83%
“…In other reports, the number of female patients was 1.9-9 times higher than that male patients. [11][12][13] Only one report from Italy showed that the number of male patients was higher than that of female patients. 23 They did not analyze the relationship between age at onset and sex.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin is a globulin with a chemical structure with antibody activity, similar to the antibody molecule, and combined treatment with glucocorticoids can effectively deliver antibodies from immunoglobulin to the patient and convert the acetylcholine receptor of immunoglobulin to the patient's own antigen [9]. Thus, it helps the patient's own acetylcholine antibody production and promotes the autoimmune response of the patient's organism, and exogenous IgG can interfere with the binding of AChR antibodies to AChR, thus protecting the ACR from being blocked by antibodies and ultimately playing an immune protective role [10]. Based on this, we have explored the effect of immunoglobulin treatment on the clinical efficacy and immune function of patients with oculomotor myasthenia gravis in children, after treatment with immunoglobulin.…”
Section: Introductionmentioning
confidence: 99%
“…None of the patients’ newborns had a history of neonatal MG. Indeed, MG antibodies binding preferentially to the fetal or the adult AChR subtype are rare but may be relevant to the clinical phenotype 16–18. Whether this is in keeping with the known expression of fetal AChRs in extraocular muscles19 merits further study.…”
Section: Discussionmentioning
confidence: 99%